Decision Support System for Alternative Selection of Family Medicinal Plants using the WEB-Based TOPSIS Method - Nurasima Wahid; Dwi Arief Prambudi; Nurlaila (TEPIAN, 2020)
Indonesia is a growing place for 80 percent of medicinal plants in the world with 28,000 plant species are grown and 1,000 species of which have been used as medicinal plants. The utilization of plant raw materials is still fixed by one type of material even though these materials can be used by various types of diseases. Family Medicinal Plants, known as "TOGA", are cultivated plants that have natural medicinal properties and can cure minor ailments that often occur in families, and now can be cultivated in the yard. The TOPSIS method was chosen because it makes it easier for users to determine alternative types of family medicinal plants or traditional medicines in the surrounding environment, called a decision support system. This research was conducted at Sari Bumi Farmer Group, Sambiloto Street RT 14 No. 24. The research period was ± 6 (six) months, from October 2018 - March 2019 which included making proposals, collecting data, making applications, and compiling reports. The "TOGA" Selection Decision Support System using the TOPSIS Method makes it easy for users to choose plants that can be used as medicine and to determine the type of medicinal plant family based on different criteria for each existing plant.